Urinary bladder carcinoma with triplicate differentiations into giant cell sarcomatoid carcinoma, squamous cell carcinoma, and papillary urothelial transitional cell carcinoma: a case report - Terada, Tadashi (BioMed Central, 2009)
The author reports a very rare and very unique urinary bladder carcinoma. This carcinoma occurred in a 68-year-old Japanese patient who underwent cystectomy for bladder tumor. The tumor was large polypoid and ulcerated one. Histologically, the tumor consisted of the following three elements: giant cell sarcomatoid carcinoma (70% in area), squamous cell carcinoma (20% in area), and papillary urothelial transitional cell carcinoma (10% in area). The former two elements were invasive into the peribladder fat tissue, while the latter one element invaded into the submucosa. There were gradual merges between the giant cell sarcomatoid element and squamous cell carcinoma element. Apparent transitions were not seen between the transitional cell carcinoma element and the giant cell sarcomatoid element or the squamous cell carcinoma element. Immunohistochemically, the giant cell sarcomatoid element was positive for various kinds of cytokeratins and vimentin while the squamous and transitional cell carcinoma elements were positive for various kinds of cytokeratins and negative for vimentin. The giant cell sarcomatoid element was free of other specific antigens. The author speculates that giant cell sarcomatoid carcinoma transdifferentiates into squamous cell carcinoma, and vice versa. The relationship between transitional cell carcinoma and the other two elements is unclear in the present case.